Case Report: Leiomyosarcoma of the right external iliac artery: a diagnostic-based study on a rare case - Olivier, Mpano; Ryash, Ahmed Abu; Yin, Weiwei; Bao, YuHui; Zhou, Qiangyong; Wang, Xi; Chen, Guorong; Yan, Xiaojian (Frontiers in Oncology, 2023)
Leiomyosarcoma (LMS) is an uncommon and aggressive form of cancer that originates in the smooth muscles. It possesses the capacity for rapid growth and often manifests with general, non-specific symptoms arising from the displacement of nearby structures rather than direct invasion. In this particular instance, an 81-year-old woman presented with right lower abdominal pain, leading to the discovery of a mass adjacent to the right external iliac artery. Diagnosing LMS typically involves employing imaging modalities like magnetic resonance imaging (MRI) and contrast-enhanced computed tomography (CT) scans. In this case, a well-defined tumor was detected through CT imaging and subsequently surgically excised. The histopathological analysis of the tumor revealed the presence of malignant spindle cells, nuclear pleomorphism, and tumor giant cells. Immunohistochemistry tests were conducted, indicating positive results for CD34 and Desmin, while CD117 and DOG1 showed negative results. It is worth noting that LMS of the right external iliac artery is an exceptionally rare occurrence, potentially resulting in delayed diagnosis and misidentification. To enhance our comprehension of this uncommon cancer, more cases with detailed information are essential.